A comprehensible machine learning tool to differentially diagnose idiopathic pulmonary fibrosis from other chronic interstitial lung diseases. Issue 9 (13th June 2022) - Furukawa, Taiki; Oyama, Shintaro; Yokota, Hideo; Kondoh, Yasuhiro; Kataoka, Kensuke; Johkoh, Takeshi; Fukuoka, Junya; Hashimoto, Naozumi; Sakamoto, Koji; Shiratori, Yoshimune; Hasegawa, Yoshinori
Abstract: Background and objective: Idiopathic pulmonary fibrosis (IPF) has poor prognosis, and the multidisciplinary diagnostic agreement is low. Moreover, surgical lung biopsies pose comorbidity risks. Therefore, using data from non‐invasive tests usually employed to assess interstitial lung diseases (ILDs), we aimed to develop an automated algorithm combining deep learning and machine learning that would be capable of detecting and differentiating IPF from other ILDs. Methods: We retrospectively analysed consecutive patients presenting with ILD between April 2007 and July 2017. Deep learning was used for semantic image segmentation of HRCT based on the corresponding labelled images. A diagnostic algorithm was then trained using the semantic results and non‐invasive findings. Diagnostic accuracy was assessed using five‐fold cross‐validation. Results: In total, 646, 800 HRCT images and the corresponding labelled images were acquired from 1068 patients with ILD, of whom 42.7% had IPF. The average segmentation accuracy was 96.1%. The machine learning algorithm had an average diagnostic accuracy of 83.6%, with high sensitivity, specificity and kappa coefficient values (80.7%, 85.8% and 0.665, respectively). Using Cox hazard analysis, IPF diagnosed using this algorithm was a significant prognostic factor (hazard ratio, 2.593; 95% CI, 2.069–3.250; p  < 0.001). Diagnostic accuracy was good even in patients with usual interstitial pneumonia patterns on HRCT and those with surgical lung biopsies. Conclusion: Using data from non‐invasive examinations, the combined deep learning and machine learning algorithm accurately, easily and quickly diagnosed IPF in a population with various ILDs. Abstract : Our comprehensible combined deep learning and machine algorithm can be used to easily, rapidly and non‐invasively diagnose and differentiate idiopathic pulmonary fibrosis from various interstitial lung diseases using non‐invasive examinations and HRCT, with high accuracy, sensitivity, specificity and kappa coefficient values.